Stock market and its liquidity: Evidence from ARDL bound testing approach in the Indian context - Sharad Nath Bhattacharya; Mousumi Bhattacharya; Sankarshan Basu (Cogent Economics & Finance, 2019)
This paper attempts to capture the relationship between stock market movements and its endogenous liquidity measures using Autoregressive Distributed-lag (ARDL) Bounds Testing Approach. We consider depth, breadth, tightness, immediacy and resiliency dimensions of market liquidity using suitable liquidity measures (proxies). Findings suggest that multidimensional liquidity measures like the volume of trade, spread, market efficiency coefficient, turnover rate, trading probability, and the stock market index are in a long-term relationship. While trading activity and market efficiency coefficient affect stock market positively, the negative impact is seen in the case of spread. The liquidity measures affect the stock market in the short run as well. We find that impact of the turnover rate on the stock market is negative in short-run but positive in the long-run. The findings are important for investors and the market participants as well who pursue loss minimization strategies. The results indicate that short-term policy interventions need not get more important than the long-term objectives of market reforms.
Keywords: C22; G10; G12; 330; stock market; liquidity; ARDL; market efficiency coefficient; spread; turnover rate